2014
DOI: 10.1016/j.jare.2013.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional linear and volumetric analysis of maxillary sinus pneumatization

Abstract: Considering the anatomical variability related to the maxillary sinus, its intimate relation to the maxillary posterior teeth and because of all the implications that pneumatization may possess, three-dimensional assessment of maxillary sinus pneumatization is of most usefulness. The aim of this study is to analyze the maxillary sinus dimensions both linearly and volumetrically using cone beam computed tomography (CBCT) to assess the maxillary sinus pneumatization. Retrospective analysis of 30 maxillary sinuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 29 publications
2
36
0
1
Order By: Relevance
“…The second major factor influencing covariation in the current study relates to maxillary sinus height, which predominantly reflects variation in inferior extension toward the alveolar region. Numerous studies (e.g., Eberhardt et al, ; Ohba et al, 2001; Ariji et al, ; Nimigean et al, ; Hamdy and Abdel‐Wahed, ) have investigated the pneumatization of the alveolar region due to clinically related factors influenced by the relative position of the sinus floor and neighboring tooth roots (root‐sinus perforation, infection, bone grafting, dental implants, etc.). Overall, these studies agree that the morphology of the sinus floor is in some way related to the dentition and upper molar roots, although the exact nature of this relationship remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second major factor influencing covariation in the current study relates to maxillary sinus height, which predominantly reflects variation in inferior extension toward the alveolar region. Numerous studies (e.g., Eberhardt et al, ; Ohba et al, 2001; Ariji et al, ; Nimigean et al, ; Hamdy and Abdel‐Wahed, ) have investigated the pneumatization of the alveolar region due to clinically related factors influenced by the relative position of the sinus floor and neighboring tooth roots (root‐sinus perforation, infection, bone grafting, dental implants, etc.). Overall, these studies agree that the morphology of the sinus floor is in some way related to the dentition and upper molar roots, although the exact nature of this relationship remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these studies agree that the morphology of the sinus floor is in some way related to the dentition and upper molar roots, although the exact nature of this relationship remains unclear. Indeed, a review of the literature suggests the depth of the sinus floor relative to the precise molar roots exhibits high inter‐individual variation (Koppe et al, ; Ariji et al, ; Nimigean et al, ; Hamdy and Abdel‐Wahed, ). In a broader evolutionary sense, Koppe et al () attribute alveolar pneumatization to a reduction in jaw size and retraction of the face beneath the cranial base.…”
Section: Discussionmentioning
confidence: 99%
“…Some evolutionary, clinical, and surgical studies have provided evidence of association between the morphology of paranasal sinuses and the surrounding bony structures (e.g., Fatu et al, ; Flanigan et al, ; Hamdy & Abdel‐Wahed, ; Park et al, ; Rahmati et al, ; Smith et al, ; Štoković et al, ; Zollikofer & Weissmann, ) and between sinuses and stature in humans (Ruf & Pancherz, ). Studies comparing different species of mammals have shown that the FS volume is positively associated with skull size (Curtis et al, ; Farke, ; Zollikofer et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In these patients maxillary sinuses are typically reduced in size and obliterated, with poor pneumatisation and increased risk of recurrent sinusitis developing [37,38]. The excessive marrow growth in the frontal, temporal and maxillary bones affect the physiological growth and pneumatisation of the paranasal sinuses, except the ethmoid sinuses, which are not involved in this process due to the absence of hematopoietic tissue.…”
Section: Discussionmentioning
confidence: 99%